2021
DOI: 10.1177/1420326x211005174
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of the effects of canopy properties on airflow and pollutant dispersion in street canyons

Abstract: The air flow and pollutant concentration fields in a street canyon affected by trees could affect the comfort and health of residents. At present, the description of the non-uniform/discontinuous distribution of leaves is difficult. In this study, the leaf distribution in the canopy was characterized by establishing non-continuous (uniform/random) algorithm based on a numerical simulation method, and the effects of canopy properties including, height, porosity and uniform/random leaf distribution, on the airfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The arbitrary polyhedral finite volume method in OpenFOAM [26,27] is used to discretize the pore-scale dynamic equations. The following procedure is used to solve the pore-scale models:…”
Section: Solution Proceduresmentioning
confidence: 99%
“…The arbitrary polyhedral finite volume method in OpenFOAM [26,27] is used to discretize the pore-scale dynamic equations. The following procedure is used to solve the pore-scale models:…”
Section: Solution Proceduresmentioning
confidence: 99%
“…14 On the other hand, controlling the diffusion of pollutants can be achieved such as by urban spatial layout 15,16 and road greening configuration. 17,18 For the influence of urban morphology, urban morphology indicators (building density, building height, plot ratio, etc.) have an important role in the diffusion of pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…The flow of air currents and the dispersal of contaminants in the canyon have been studied extensively over the past few decades. The methods commonly used in the research are field measurement [7], wind tunnel experiment [8][9][10], and numerical simulation of computational fluid dynamics (CFD) [11][12][13][14][15][16][17]. Previous studies have focused on the following aspects: the aspect ratio of the street canyon; aspect ratio is a critical parameter, and the structure of the flow field in the canyon with different aspect ratios is not precisely the same; the researchers found that when the aspect ratio is small, there is only one clockwise vortex in the street canyon, and when the aspect ratio becomes larger, there are multiple vortices in the canyon and the direction will be changed [18][19][20].…”
Section: Introductionmentioning
confidence: 99%